Leveraging SWOT Analysis in IS/IT Strategy for Enhancing Hospital Quality - Kamarudin, Kamarudin (Universitas Aisyiyah Surakarta, 2024)
The research conducted at the Datu Sanggul Hospital in Rantau focuses on developing a strategic plan for enhancing the quality of healthcare services through Information System (IS) and Information Technology (IT) implementation. The study aims to address the challenges faced by the hospital in optimizing its Management Information System and Medical Record (SIM & RM) unit. By utilizing the Ward & Peppard framework, the research progresses through stages including problem formulation, data collection, and strategy formulation. Through interviews, focus group discussions, and data analysis, the current business strategies and IT infrastructure are evaluated. External factors such as PEST analysis and Five Forces analysis are also considered to understand the hospital's position in the industry. The findings from these analyses serve as inputs for the SWOT analysis, which helps in identifying the hospital's current standing and areas for improvement. The study further delves into developing IS business strategies and IT roadmap planning based on critical success factors and business needs. By aligning IS/IT strategies with business goals, the research aims to provide recommendations for enhancing the hospital's information system infrastructure and management practices.